2016
DOI: 10.1111/jiec.12478
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of U.S. and Japanese Consumers’ Perceptions of Remanufactured Auto Parts

Abstract: This study compares U.S. and Japanese consumers' perceptions of remanufactured auto parts. Remanufactured parts have a long history and enjoy continuing success in the U.S. domestic aftermarket. In contrast, although Japan's domestic aftermarket is growing, it remains comparatively underdeveloped. This research examines whether customers' perceptions of remanufactured products explain their lower acceptance in Japan. Our Internet survey of 440 U.S. and 300 Japanese respondents examined their knowledge of reman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 75 publications
2
46
0
Order By: Relevance
“…Ambiguity tolerance is a prominent personality trait in the context of buying remanufactured products as many individuals are unfamiliar with remanufactured products. There has been empirical evidence directly or indirectly confirming the positive correlation of ambiguity tolerance with consumer attitude and behavioral intention (Johnson, Tian, & Lee, ; Matsumoto, Chinen, & Endo, ; Yoon & Choo, ). Jena and Sarmah () found that ambiguity tolerance is directly related to both consumer perceptions and the intention to pay a premium for returning the used products.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Ambiguity tolerance is a prominent personality trait in the context of buying remanufactured products as many individuals are unfamiliar with remanufactured products. There has been empirical evidence directly or indirectly confirming the positive correlation of ambiguity tolerance with consumer attitude and behavioral intention (Johnson, Tian, & Lee, ; Matsumoto, Chinen, & Endo, ; Yoon & Choo, ). Jena and Sarmah () found that ambiguity tolerance is directly related to both consumer perceptions and the intention to pay a premium for returning the used products.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Besides the factors fostering or hindering the consumption of specific solutions, some authors have explored perceptions of different forms of circular solutions such as Armstrong et al [124,125], who investigated what aspects influenced the positive or negative perceptions of hypothetical scenarios. Matsumoto [123] compared the perceptions of remanufactured products between United States (U.S.) and Japanese consumers regarding factors such as knowledge, price, and risks, among others. Other authors focussed on types of consumer and their acceptance of circular solutions.…”
Section: Other Psychological Factorsmentioning
confidence: 99%
“…This contribution follows closely the extensive investigation of consumers' perceptions of remanufactured auto parts by Matsumoto et al [29,30], and applies their established methodology in an effort to uncover relevant findings in a European context. Previous studies by Matsumoto et al [28][29][30] have focused in US and Asian markets, but the European perspective is still missing from similar literature regarding remanufactured auto parts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on remanufactured automotive parts have focused on the operational challenges and drivers of OEMs [42] and small-and medium-sized independent remanufacturers [35]. Very few studies have focused on consumer perceptions of remanufactured parts, mostly in the US and Asian markets [28][29][30], while a European perspective is still missing from literature regarding this topic.…”
Section: Introductionmentioning
confidence: 99%